2019
DOI: 10.1021/acs.jafc.9b01276
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Novel Triazole Derivatives as Strigolactone Biosynthesis Inhibitors

Abstract: Strigolactones (SLs) are one of the plant hormones that control several important agronomic traits, such as shoot branching, leaf senescence, and stress tolerance. Manipulation of the SL biosynthesis can increase the crop yield. We previously reported that a triazole derivative, TIS108, inhibits SL biosynthesis. In this study, we synthesized a number of novel TIS108 derivatives. Structure–activity relationship studies revealed that 4-(2-phenoxyethoxy)-1-phenyl-2-(1H-1,2,4-triazol-1-yl)­butan-1-one (KK5) inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…Triflumizole treatment slightly but significantly reduced plant height in a dose-dependent manner ( Figure 5). TIS108 and KK5 do not reduce the height of rice plants when applied at 50 µM [21]. The collective findings indicate that triflumizole seems to inhibit the enzymatic activity of Os900 as well as the activities of other P450 proteins in the gibberellin and/or brassinosteroid biosynthesis pathways.…”
Section: Side Effect Of Triflumizolementioning
confidence: 85%
See 1 more Smart Citation
“…Triflumizole treatment slightly but significantly reduced plant height in a dose-dependent manner ( Figure 5). TIS108 and KK5 do not reduce the height of rice plants when applied at 50 µM [21]. The collective findings indicate that triflumizole seems to inhibit the enzymatic activity of Os900 as well as the activities of other P450 proteins in the gibberellin and/or brassinosteroid biosynthesis pathways.…”
Section: Side Effect Of Triflumizolementioning
confidence: 85%
“…The triazole-containing compound TIS13 was identified as the lead compound for SL biosynthesis inhibitors [19]. A structure-activity relationship study based on the structure of TIS13 identified two potent and specific SL biosynthesis inhibitors, TIS108 and KK5 [20,21]. In addition to TIS13, of seven azole derivatives identified as fungicides, tebconazole was It has been reported that nitrogen-containing heterocyclic compounds, including imidazole and triazole groups, have inhibitory activities against various CYPs in mammals, microorganisms, and plants [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Although TIS108 is an inhibitor of P450 cytochrome monooxygenases and thus supposed to be an antagonist of strigolactone function, previous reports have confirmed its inhibitory effect to hypocotyl elongation ( Kawada et al, 2019 , 2020 ). On this basis, the follow-up effects of TIS108 on cortical microtubule organization and dynamics are in line with its observed effects on hypocotyl growth.…”
Section: Discussionmentioning
confidence: 96%
“…A triazole-type strigolactone biosynthesis inhibitor, TIS108 (Chiralix, Netherlands), an effective tool for regulating strigolactone production in Arabidopsis (Ito et al, 2013) with some limitations (Kawada et al, 2019(Kawada et al, , 2020, was dissolved in pure acetone prior to use to make a 10 mM stock solution further diluted to 3 µM and 10 µM final concentrations and added to agarose-solidified 1 /2 MS medium. A 0.01% v/v acetone solution in water was used as a mock control for both GR24 and TIS108.…”
Section: Chemical Treatmentmentioning
confidence: 99%
“…Particularly, the compound TIS108 (Figure 8) proved to reduce the production of SLs in both rice and tomato with no adverse effects on tillering or shoot branching, and, moreover, it reduced parasitism of O. minor and S. hermonthica (greenhouse pot test) [101]. This compound inhibited the formation of 4-deoxyorobanchol in rice in a dose-dependent manner in the range of 10−100 nM [102]. TIS108 can be likewise interesting in the suicidal germination context, since it stimulates rapidly the germination of high percentages of Phelipanche aegyptiaca seeds if the preconditioning period in water (common in germination bioassays) is not applied to the seeds [103].…”
Section: Applications Of Strigolactones In Agriculturementioning
confidence: 97%